2021
DOI: 10.3233/mas-210533
|View full text |Cite
|
Sign up to set email alerts
|

The time series regression analysis in evaluating the economic impact of COVID-19 cases in Indonesia

Abstract: This study aims to determine the impact of COVID-19 cases in Indonesia on the USD/IDR exchange rate using the Transfer Function Model and Vector Autoregressive Moving-Average with Exogenous Regressors (VARMAX) Model. This paper uses daily data on the COVID-19 case in Indonesia, the USD/IDR exchange rate, and the IDX Composite period from 1 March to 29 June 2020. The analysis shows: (1) the higher the increase of the number of COVID-19 cases in Indonesia will significantly weaken the USD/IDR exchange rate, (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…If VAR models addressing autoregressive effects do not provide a reasonable fit, it might be worthwhile adding more variables to the picture or considering VARIMA models which incorporate both autoregressive and moving average effects for several variables (Mukhaiyar et al, 2021). However with either increasing dimensionality of VAR or introducing moving average terms in VARIMA, there is a danger of models becoming overparameterized and non-identifiable (Guibert et al, 2019).…”
Section: Var (Vector Autoregression)mentioning
confidence: 99%
“…If VAR models addressing autoregressive effects do not provide a reasonable fit, it might be worthwhile adding more variables to the picture or considering VARIMA models which incorporate both autoregressive and moving average effects for several variables (Mukhaiyar et al, 2021). However with either increasing dimensionality of VAR or introducing moving average terms in VARIMA, there is a danger of models becoming overparameterized and non-identifiable (Guibert et al, 2019).…”
Section: Var (Vector Autoregression)mentioning
confidence: 99%
“…On the other hand, the ARCH model, which accommodates the element of heteroscedasticity and exogenous variable which make the high volatility of process, is widely developed in economic problems. The impact of Covid-19 as the exogenous factor to the economic sector be explored by [18]. Sometimes the exogeneous factor cause a point of change happen and it should be detected [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, [18] studied time series regression with a unit root, and the results showed that the method outlined in the section for the refinement of first-order asymptotic theory may be applied in general time series models with unit roots. Furthermore, [19] investigated a time-series regression analysis to evaluate the economic impact of COVID-19 cases in Indonesia using the transfer function model and vector autoregressive moving average with exogenous regressors (VARMAX) model. The results show that an increase in the number of COVID-19 cases in Indonesia significantly affected the USD/IDR exchange rate.…”
mentioning
confidence: 99%
“…is χ 2 (2) = 3.8983 with p − v alue = 0.1424, where Ho is rejected as the p − v alue is greater than α = 0.05. Table3presents the iteration procedure for ρ convergence in estimating the Cochrane-Orcutt parameters of the model presented in Equation(19). Table4presents the model performance for various measures; however, the most commonly used measure is the coefficient of determination (R 2 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation